Body composition and bone health in adolescents after Roux‐en‐Y gastric bypass for severe obesity. Issue 3 (12th April 2016) - Beamish, A. J.; Gronowitz, E.; Olbers, T.; Flodmark, C.‐E.; Marcus, C.; Dahlgren, J.
Summary: Background: Laparoscopic Roux‐en‐Y gastric bypass (RYGB) causes changes in body composition and bone metabolism, yet little is known about effects in adolescents. Objectives: The objective of this study was to report dual‐energy X‐ray absorptiometry measures and serum bone markers, hypothesizing that bone turnover increases after surgery. Methods: Inclusion criteria included the following: age 13–18 years and body mass index (BMI) >35 kg/m 2 . Seventy‐two adolescents (22 boys; mean age 16.5 years; BMI 44.8 kg/m 2 ) undergoing RYGB underwent dual‐energy X‐ray absorptiometry and serum bone marker analyses preoperatively and annually for 2 years. Results: Mean BMI reduction at 2 years was 15.1 kg/m 2 . Body composition changes included a reduction in fat mass (51.8% to 39.6%, p  < 0.001) and relative increase in lean mass (47.0% to 58.1%, p  < 0.001). In contrast to previous studies in adults, adolescent boys lost a greater percentage of their body fat than girls (−17.3% vs. −9.5%, p  < 0.001). Individual bone mineral density Z‐scores (BMD‐Z) at baseline were within or above the normal range. The mean (SD) BMD‐Z was 2.02 (1.2) at baseline, decreasing to 0.52 (1.19) at 2 years. Higher concentrations of serum CTX ( p  < 0.001) and osteocalcin ( p  < 0.001) were observed in boys throughout the study period. Levels rose in the first year, before decreasing modestly in the second. Levels of serum markers of bone synthesis and resorption were higher in boys, whose skeletal maturity occurs later than girls'. Conclusions: Differences in body fat and lean mass proportions were observed according to sex following RYGB. Bone turnover increased, and BMD decreased to levels approaching a norm for age. Long‐term outcome will determine the clinical relevance.